Beyond NAMs versus animal models: Context of use as the governing framework for integrated nonclinical strategies in drug development - Stefano Gaburro; Brian Berridge; Nicholas W. Kelley; Eckhard von Keutz; Marc Ferrer; Clive Roper; Michael J. Fossler; Jeffrey J. Bajramovic; Jean-Pierre Valentin; Timothy McGovern; Todd Bourcier; Ronald L. Wange; et al. (Regulatory Toxicology and Pharmacology, 2026)

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Welfare Indicators for Aquaculture Research: Toolboxes for Five Farmed European Fish Species - Chris Noble; Wout Abbink; René Alvestad; László Ardó; Marie‐Laure Bégout; Nina Bloecher; Erik Burgerhout; Josep Calduch‐Giner; Mauro Chivite‐Alcalde; Petr Císař; Evan Durland; Åsa M. Espmark; et al. (Reviews in Aquaculture, 2026)
Refining approaches to measuring, monitoring and appraising animal welfare in aquaculture research is key to (i) protecting and optimizing it, (ii) documenting the severity of how and when it deviates, and (iii) ensuring good scientific quality, reliable results and reproducibility, amongst other factors. However, different fish species and life stages can have varying welfare needs and assessing their welfare can be challenging. An array of welfare indicators (WIs) can be utilized when documenting fish welfare, and there is currently little consensus on which WIs are most applicable to the key fish species used in European aquaculture research. The aim of this review is to propose updated, fit for purpose and comprehensive WI toolboxes for aquaculture research involving Atlantic salmon ( Salmo salar ), rainbow trout ( Oncorhynchus mykiss ), European seabass ( Dicentrarchus labrax ), gilthead seabream ( Sparus aurata ), and the common carp ( Cyprinus carpio ). Where possible, these toolboxes will also include life‐stage considerations. It also provides information on utilizing WIs in deciding humane end‐points as well as information on how to sample different types of indicators. The review closes with information on how digitalization can affect the collection, collation and analysis of WI data in aquaculture research, including both practical and theoretical considerations. The toolboxes incorporate a range of WIs that go beyond those required for legally safeguarding fish welfare in both laboratory and operational experimental facilities in the current European 2010/63/EU Directive on the protection of animals used for scientific purposes and its amendment, the Commission Delegated Directive (EU) 2024/1262.

In silico & in vitro approaches suggest osteoclastogenesis induction underlying fractures in Entrectinib-treated children - Sabrina Ehnert; Andreas K. Nüssler; Kevin A. Schulz; Alison Cardenas; Georgina Meneses-Lorente; Sam McCallum; Sabine Fürst-Recktenwald; Adrian Roth (Archives of Toxicology, 2025)
Entrectinib, a potent, CNS-active, TRK and ROS1 inhibitor is associated with occurrence of bone fractures, particularly in pediatric patients. We embarked on computer-guided and experimental investigations to identify the underlying mechanism that should help safe dosing of children receiving this drug. An artificial intelligence (AI)-based approach was used to allow for hypothesis generation regarding drug effects in a clinical setting and mechanistic insights on safety and efficacy. This was followed by confirmatory in vitro studies using human bone cell cultures. The AI-based hypothesis suggested an effect via inhibition of TRK and JAK2, as molecular targets of Entrectinib, underlying the fractures. Subsequent experiments using human bone cells showed that Entrectinib reduced markers of osteoblastic- and mineralization-activity. Conversely, Entrectinib had stimulating effects on osteoclast function indicative of bone resorption. 3D osteoblast-osteoclast cultures revealed reduced stiffness after Entrectinib treatment and this was pronounced in the absence of 17β-estradiol, characteristic for juvenile bone. Pathway analysis revealed inhibition of bone growth regulators TGF-β and BMP which is suggested to underlie the in silico-proposed JAK2 effect. Pre-treatment with Vitamin D led to partially restored osteoblast function in vitro, while osteoclast function was suppressed. These experiments suggest an on-target effect of Entrectinib underlying increased fractures particularly in children with developing bones, offering potential mitigation strategies if these observations can be confirmed with data from ongoing clinical trials.

High-speed scattered-light imaging for sizing respiratory droplets - Adrian Roth; David Frantz; Mehdi Stiti; Edouard Berrocal (Journal of Aerosol Science, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Concurrent isolation of hepatic stem cells and hepatocytes from the human liver - Serene M. L. Lee; Cristina Bertinetti-Lapatki; Tobias S. Schiergens; Karl-Walter Jauch; Adrian B. Roth; Wolfgang E. Thasler (In Vitro Cellular & Developmental Biology - Animal, 2020)
Hepatocytes differentiated from induced pluripotent stem cells or stem cells have the potential to be representative in vitro models of the human liver for research as well as early safety assessment programs. However, up until now, there has been no definitive proof that differentiated hepatocytes recapitulate the phenotype and functional characteristics of primary hepatocytes from the same individual. Thus, a method for the concurrent isolation of hepatocytes and hepatic stem cells is presented here to provide the cells necessary for the evaluation of the required benchmarking. The method presented here generated high-quality hepatocytes with a purity of 94 ± 1% and a high percentage viability of 79 ± 2%. Furthermore, the hepatic stem cells isolated were found to be actively proliferating and have a purity of 98 ± 1%. Thus, these isolated cells can be used as a powerful tool for the validation of differentiated hepatocyte in vitro models.

A model-based assay design to reproduce in vivo patterns of acute drug-induced toxicity - Lars Kuepfer; Olivia Clayton; Christoph Thiel; Henrik Cordes; Ramona Nudischer; Lars M. Blank; Vanessa Baier; Stephane Heymans; Florian Caiment; Adrian Roth; David A. Fluri; Jens M. Kelm; et al. (Archives of Toxicology, 2018)

Current limitations and future opportunities for prediction of DILI from in vitro - Christoph Funk; Adrian Roth (Archives of Toxicology, 2017)

Model-based assessment of erlotinib effect in vitro measured by real-time cell analysis - Stephan Benay; Christophe Meille; Stefan Kustermann; Isabelle Walter; Antje Walz; P. Alexis Gonsard; Elina Pietilae; Nicole Kratochwil; Athanassios Iliadis; Adrian Roth; Thierry Lave (Journal of Pharmacokinetics and Pharmacodynamics, 2015)